2022
DOI: 10.3390/ijms23105817
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophin Signaling Impairment by Viral Infections in the Central Nervous System

Abstract: Neurotrophins, such as nerve growth factor (NGF), brain-derived neurotrophic factor (BDNF), and neurotrophin 3 (NT-3), NT-4, and NT-5, are proteins involved in several important functions of the central nervous system. The activation of the signaling pathways of these neurotrophins, or even by their immature form, pro-neurotrophins, starts with their recognition by cellular receptors, such as tropomyosin receptor kinase (Trk) and 75 kD NT receptors (p75NTR). The Trk receptor is considered to have a high affini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 160 publications
(345 reference statements)
0
12
0
Order By: Relevance
“…NGFR present on the cell surface reportedly recognizes the NGF, BDNF, NT-3, and NT-4 signals that regulate various biological functions of the cells [21,22]. The cell-to-cell communication assay conducted in the present study revealed that NGF-NGFR communication was the only signal in the tumor tissues of HCC patients.…”
Section: Discussionmentioning
confidence: 51%
“…NGFR present on the cell surface reportedly recognizes the NGF, BDNF, NT-3, and NT-4 signals that regulate various biological functions of the cells [21,22]. The cell-to-cell communication assay conducted in the present study revealed that NGF-NGFR communication was the only signal in the tumor tissues of HCC patients.…”
Section: Discussionmentioning
confidence: 51%
“…NGFR present on the cell surface reportedly recognizes the NGF, BDNF, NT-3, and NT-4 signals that regulate various biological functions of the cells. 22,23 The cell-to-cell communication assay conducted in the present study revealed that NGF-NGFR communication was the only signal in the tumor tissues of HCC patients. This result indicated no possibility of communication between NGFR and the other three ligands.…”
Section: Discussionmentioning
confidence: 58%
“…Several studies shed light on how viral infections and vaccines affect the central nervous system. Bohmwald et al (2022) highlight the importance of neurotrophins in the CNS function, with viral infections impairing their signaling [ 36 ]. Azoulay et al (2020) underscore BDNF's role during recovery from SARS-CoV-2 infection [ 37 ], while Demir et al (2022) delve into COVID-19’s prolonged cognitive effects and the possible involvement of BDNF [ 38 ].…”
Section: Discussionmentioning
confidence: 99%